Preparing for Home: a before-and-after study to investigate the effects of a neonatal discharge package aimed at increasing parental knowledge, understanding and confidence in caring for their preterm infant before and after discharge from hospital - Ingram, J; Blair, P; Powell, J; Manns, S; Burden, H; Pontin, D; Redshaw, M; Beasant, L; Rose, C; Johnson, D; Gaunt, D; Fleming, P (NIHR Journals Library, 2016)
Background: Improved survival and shorter length of stay (LOS) for preterm infants, together with poorly organised discharge planning in some neonatal units, leaves many parents ill prepared to take their babies home, with increased use of out-of-hours services. Despite the importance accorded to family-orientated neonatal care by the Department of Health and the National Institute for Health and Care Excellence, few neonatal units offer structured, family-orientated discharge planning. Objectives To implement a parent-orientated discharge planning approach (Train-to-Home package) for preterm infants and investigate the effects on parental self-efficacy scores, infants’ LOS and change in costs associated with use of health-care resources in the 8 weeks after discharge, before and after implementation. Design A before-and-after study, investigating the effects of Train-to-Home package during two 11-month periods, immediately before and after its implementation. Setting Four local neonatal units in South West England. Participants Infants without major anomalies, born at 27–33 weeks’ gestation, admitted to the participating units, and their parents. Train-to-Home intervention A parent-orientated package that incorporated approaches to improving parents’ involvement in, and understanding of, their baby’s needs. It comprised a train graphic and supporting care pathways to facilitate parents’ understanding of their baby’s progress through the neonatal unit, combined with improved estimation, soon after hospital admission, of the baby’s likely discharge date. Main outcome measures Primary – Perceived Maternal Parenting Self-Efficacy (PMPS-E) scores before and after implementing the Train-to-Home package; secondary – infant LOS and health-care utilisation after discharge. Results We recruited 128 and 117 infants, respectively, in phase 1 (before implementation) and phase 2 (after implementation). In phase 2, parents reported improved understanding of babies’ progress, and preparedness for discharge, although PMPS-E scores did not change. The number of visits to emergency departments (EDs) fell from 31 in phase 1 to 20 in phase 2 (p < 0.05), with a significant reduction in associated health-care costs (from £3400 to £2200; p < 0.05) after hospital discharge. LOS did not change, but in both phases of the study > 50% of infants went home at > 3 weeks before their estimated date of delivery. Many nurses felt that the estimated discharge dates were over-optimistic, despite being based upon recent local data, and accurately predicting discharge dates for almost 75% of babies in the study. Harms No adverse consequences were identified. Conclusions The very early discharge of most babies made further shortening of LOS very difficult to achieve. Despite the lack of change of the parental self-efficacy scores, parents reported that their understanding and confidence in caring for their infants were improved by the Train-to-Home package, and the reduction in ED attendance and associated costs supports this assessment. The present study was limited by the tight time constraints for implementation, limited cascading of staff training and lack of staff confidence in the estimated dates of discharge. Future work Provision of the Train-to-Home package as a web-based system, allowing individual neonatal units and parents to access and use the materials, may allow more effective implementation in the future.